De novo Absence Status Epilepticus in a pediatric cohort: Electroclinical pattern in a multicenter Italian patients cohort. (December 2019) - Pepi, C.; Cesaroni, E.; Striano, P.; Maiorani, D.; Pruna, D.; Cossu, S.; Di Capua, M.; Vigevano, F.; Specchio, N.; Cusmai, R.
Abstract: Purpose: Absence Status epilepticus (AS) is a form of Non Convulsive Status Epilepticus defined as a prolonged, generalized and non-convulsive seizure, with an altered content of consciousness. We aim to describe a group of healthy children, who presented recurrent and unprovoked de novo AS as the only manifestation of their epilepsy, with an excellent response to antiepileptic drugs. Method: We retrospectively reviewed the electroclinical and genetic features of 13 pediatric patients, referring to our epilepsy centers from 2005 to 2019, on the following criteria: (1) regular psychomotor development, (2) one or more unprovoked AS as the only epileptic manifestation, (3) normal blood testing, (4) normal neuroimaging, (5) EEG recording, (6) available follow-up (1–14 years). Results: Patients are 7 females and 6 males, aged 7–22, with a mean age at AS onset of 9, 3 years. All of them started an antiepileptic therapy, with an excellent response to Valproic Acid (VPA) or Ethosuximide (ETS). 5 patients did not start the therapy immediately after the first AS and they presented recurrent AS (from 2 to 4 episodes). 10 of them performed aCGH, karyotype, NGS panel or Whole Exome Sequencing. Conclusions: We suggest that de novo AS may be a well-defined age-related and self-limited epilepsy syndrome, with a good prognosis and excellent response to therapy, but it comes with a high risk of relapsing if not adequately treated with antiepileptic drugs.